Prevalence and determinants of hypertension in apparently healthy schoolchildren in India: A multi-center study. (29th August 2020) - Narang, Rajiv; Saxena, Anita; Desai, Ankush; Ramakrishnan, Sivasubramanian; Thangjam, Rajendra S; Kulkarni, Snehal; Narvencar, Kedareshwar; e Costa, Ana K Jacques'; Dias, Amit; Sukharamwala, Ritesh; Cleland, John
Abstract: Background: Hypertension in children is often under recognized, especially in developing countries. Data from rural areas of developing countries is particularly lacking. Objectives: To study prevalence of hypertension and its determinants in apparently health school children from predominantly rural populations of India. Methods: Apparently healthy schoolchildren ( n  = 14, 957) aged 5–15 years (mean (standard deviation) age 10.8 (2.8) years; 55.5% boys) at four predominantly rural sites in separate states of India were studied. Systolic and diastolic blood pressures were recorded by trained staff in addition to age, gender, height, weight, type of school and season. Waist circumference was also recorded in 12, 068 children. Geographic location and type of school (government, government-aided or private) were used to determine socio-economic status. Results: Systolic and/or diastolic hypertension was present in 3443 (23%) children. Systolic hypertension was present in 13.6%, diastolic hypertension in 15.3% and both in 5.9%. Isolated systolic hypertension was present in 7.7% while isolated diastolic hypertension was present in 9.4%. On univariate analysis, age, gender, geographical location, socio-economic status, season and anthropometric parameters (z-scores of height, weight and waist circumference, waist/height ratio and body mass index) were all significantly related to risk of hypertension ( p  < 0.0001 for each). Similar association was observed with weight group (normal, overweight and obese). Multiple regression analysis showed lower age, female gender, richer socio-economic status, certain geographical locations, higher weight and larger waist circumference to be independently associated with a greater risk of hypertension. Conclusion: There is a high prevalence of hypertension in apparently healthy schoolchildren even in predominantly rural areas of India. Screening and management programs targeted to high risk groups identified may prove cost-effective.